Perbandingan Kualitas Daging Itik Magelang, Itik Pengging Dan Itik Tegal - Hidayati, Nuke Nur; Yuniwarti, Enny Yusuf Wachidah; Isdadiyanto, Sri (Bioma : Berkala Ilmiah Biologi, 2016)
Local ducks in Indonesia there was several kinds, for example Tegal ducks, Magelang ducks and Pengging duck each having morphology different of duck. Research on the quality meat of ducks that includes ash content, water content, carbohydrate content, fat content, protein content, and muscle cell diameter of femoral ducks important to know quality meat of each duck. This study aimed to analyzed the differences types of ducks on the chemical content of meat and femoral muscle histology of diameter cell at Tegal ducks, Magelang ducks and Pengging ducks. Ducks were used in this study maintained in the Central Breeding and Raising Ducks Work Unit Non Ruminant Livestock Banyubiru, Ambarawa. The duck six month old was analyzed chemical content of meat and measuring diameter of femoral muscle cells. Duck samples taken from three different types of ducks that Tegal duck,Pengging duck and Magelang duck, of each type of sample taken many ducks as 6 tails. Data were analyzed using analysis of variance (ANOVA). If the data were analyzed contained a real difference, continued by the Least Significant Differences Test (LSDT) at 95% confidence level. The results showed that no significant difference in all variables, from the result has been concluded that differences type of ducks not affect the chemical contents of duck meat and diameter of femoral muscle cells.Â Keywords: Local Ducks in Central Java, Quality of Meat, Muscle Cell Diameter Femoral Ducks.